Cytokine Overproduction and Immune System Dysregulation in alloHSCT and COVID-19 Patients - Lange, Andrzej; Lange, Janusz; Jaskuła, Emilia (Frontiers in Immunology, 2021)
The COVID-19 pathomechanism depends on (i) the pathogenicity of the virus, (ii) ability of the immune system to respond to the cytopathic effect of the virus infection, (iii) co-morbidities. Inflammatory cytokine production constitutes a hallmark of COVID-19 that is facilitated by inability of adaptive immunity to control virus invasion. The effect of cytokine release syndrome is deleterious, but the severity of it depends on other confounding factors: age and comorbidities. In this study, we analyze the literature data on the post-transplant course of allogeneic hematopoietic stem cell transplanted (alloHSCT) patients, which is affected by generated inflammatory cytokines. The sequence of events boosting cytokine production was analyzed in relation to clinical and laboratory data highlighting the impact of cytokine generation on the post-transplant course. The collected data were compared to those from studies on COVID-19 patients. The similarities are: (i) the damage/pathogen-associated molecular pattern (DAMP/PAMP) stage is similar except for the initiation hit being sterile in alloHSCT (toxic damage of conditioning regimen) and viral in COVID-19; (ii) genetic host-derived factors play a role; (iii) adaptive immunity fails, DAMP signal(s) increases, over-production of cytokines occurs; (iv) monocytes lacking HLADR expression emerge, being suppressor cells hampering adaptive immunity; (v) immune system homeostasis is broken, the patient’s status deteriorates to bed dependency, leading to hypo-oxygenation and malnutrition, which in turn stimulates the intracellular alert pathways with vigorous transcription of cytokine genes. All starts with the interaction between DAMPs with appropriate receptors, which leads to the production of pro-inflammatory cytokines, the inflammatory process spreads, tissue is damaged, DAMPs are released and a vicious cycle occurs. Attempts to modify intracellular signaling pathways in patients with post alloHSCT graft vs host disease have already been undertaken. The similarities documented in this study show that this approach may also be used in COVID-19 patients for tuning signal transduction processes to interrupt the cycle that powers the cytokine overproduction.